2005
DOI: 10.1002/joc.1211
|View full text |Cite
|
Sign up to set email alerts
|

Long-term climate change and surface versus underground temperature measurements in Paris

Abstract: Careful temperature measurements performed from 1783 to 1852 in underground galleries, 28 m below the Paris Observatory, are compared with current measurements performed in a limestone quarry, 20 m below ground surface, and with local and European surface temperature records. When averaged using a backward 11-year moving window, the surface temperature time series looks similar and exhibits the already well-known 1°C temperature increase over the last century. In addition, since about 1987, a steeper increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…1), with pillars left in place to support the roof. About 4 m of the rock has been exploited, but most of the floor area is covered by about 2 m of filling from quarry waste, so that the mean distance between floor and ceiling is about 2 m. The average air temperature is 12.5 C, slowly increasing with time (Perrier et al, 2005a;Crouzeix et al, 2003), with an annual variation of the order of 0.04 C peak to peak. Relative humidity in the air ranges from 99.2 AE 0.1% to 99.8 AE 0.1% in most of the quarry.…”
Section: The Site and Experimental Methodsmentioning
confidence: 99%
“…1), with pillars left in place to support the roof. About 4 m of the rock has been exploited, but most of the floor area is covered by about 2 m of filling from quarry waste, so that the mean distance between floor and ceiling is about 2 m. The average air temperature is 12.5 C, slowly increasing with time (Perrier et al, 2005a;Crouzeix et al, 2003), with an annual variation of the order of 0.04 C peak to peak. Relative humidity in the air ranges from 99.2 AE 0.1% to 99.8 AE 0.1% in most of the quarry.…”
Section: The Site and Experimental Methodsmentioning
confidence: 99%
“…In winter, natural ventilation proceeds through the main vertical access pit (PERRIER et al, 2002;2005a). The average air temperature is 12.5°C, slowly increasing with time (PERRIER et al, 2005b), with an annual variation of the order of 0.04°C peak-to-peak. Relative humidity varies from 99.2 to 99.8% in most of the quarry.…”
Section: Experimental Set-ups In the Vincennes Quarry And The Paris Omentioning
confidence: 99%
“…The site is located 28 m below ground surface, in the same geological formation as the Vincennes quarry, in a cavity used in the XVIII th century for precise underground temperature measurements (Cassini, J.-D. manuscript AD5.22;PERRIER et al, 2005b). The cavity is now cemented and has a volume of 60 m 3 (width 2.5 m, depth 10 m, and height 2.4 m).…”
Section: Experimental Set-ups In the Vincennes Quarry And The Paris Omentioning
confidence: 99%
“…In Paris, which has had a long-term urban environment and heavy water infiltration, it is revealed that the temperature increase closely matches the urban air temperature increase. Perrier et al (2005), using the deep-soil temperature in the underground quarry in Vincennes, near Paris, observed temperatures greater than eighteenth and nineteenth century extrapolated values below the Paris Observatory by 0.9 • C. This increase must include some contribution from the UHI. However, the agreement with the surface temperatures suggests that this contribution is not dominating.…”
Section: Introductionmentioning
confidence: 97%